Pengembangan Denah Kantin UNJ_Citra Amalia dan Annisa Nurliza (Revisi) - Jannah, Citra Amalia Riyadlul; Sahara, Siti; Nurliza, Annisa (Jurnal Ilmiah Global Education, 2024)
The canteen has an important role as a supporting facility for campus activities, and students want the canteen to be a comfortable dining and drinking room. This study aims to explain about all canteens located on Campus A and B of Jakarta State University. The presence of several canteens in different locations causes confusion as to where the canteens are located, especially those on campuses A and B of Jakarta State University. The emergence of this problem prompted the author to find a solution, namely the creation of a canteen plan website for Campus A and B of Jakarta State University. The type of research used involves research and development called Research and Development (R&D). In this study, a website product was created with a development model using ADDIE (Analytic, Design, Development, Implement, Evaluation) which consists of five media stages to help students, lecturers, and visitors find restaurants more easily. Based on the results of the research, the existence of this website can make it easier for students, lecturers, and visitors to find out where the canteen is located at the State University of Jakarta by only accessing using a smartphone or computer / laptop connected to the internet.